1992
DOI: 10.1126/science.1439822
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Transcriptional Activation by a Metabolic Intermediate: Activation by Leu3 Depends on α-Isopropylmalate

Abstract: In the absence of the leucine biosynthetic precursor alpha-isopropylmalate (alpha-IPM), the yeast LEU3 protein (Leu3p) binds DNA and acts as a transcriptional repressor in an in vitro extract. Addition of alpha-IPM resulted in a dramatic increase in Leu3p-dependent transcription. The presence of alpha-IPM was also required for Leu3p to compete effectively with another transcriptional activator, GAL4/VP16, for limiting transcription factors. Therefore, the addition of alpha-IPM appears to convert a transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 17 publications
7
88
1
Order By: Relevance
“…Activity of a number of zinc cluster proteins is controlled by intermediary metabolites (for a review, see Sellick and Reece 2005). For example, the activity of the zinc cluster proteins Leu3 and Lys14 is controlled by intermediary metabolites of leucine and lysine biosynthesis, respectively (Feller et al 1994;Feller et al 1999;Sze et al 1992). In contrast, our unpublished results showed that activation by Uga3 is not dependent on the presence of GABA metabolites since no reduction of reporter activity is observed in strains Duga1 and Duga2, which are unable to catabolize GABA.…”
Section: Discussioncontrasting
confidence: 48%
“…Activity of a number of zinc cluster proteins is controlled by intermediary metabolites (for a review, see Sellick and Reece 2005). For example, the activity of the zinc cluster proteins Leu3 and Lys14 is controlled by intermediary metabolites of leucine and lysine biosynthesis, respectively (Feller et al 1994;Feller et al 1999;Sze et al 1992). In contrast, our unpublished results showed that activation by Uga3 is not dependent on the presence of GABA metabolites since no reduction of reporter activity is observed in strains Duga1 and Duga2, which are unable to catabolize GABA.…”
Section: Discussioncontrasting
confidence: 48%
“…The recent structural study on Ets-1 suggests that a C-terminal domain interacts within an N-terminal inhibitory region (15). In yeast, Leu3p is transcriptionally active only in the presence of ␣-isopropylmalate (66). A model has been proposed in which interaction of the central part with the C-terminal activation domain prevents activation of Leu3p until an ␣-isopropylmalate-induced conformational change occurs (77).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, not only isoamyl alcohol and isoamyl acetate increased in this mutant: the production of total diacetyl during fermentation was also about 3 times higher in the mutant CMBSPV03TFL, compared to CMBSPV03. This could be explained by altered expressions, caused by the activated transcriptional factor Leu3p, of ILV2 and ILV5, which encode the α-acetolactate synthase and the α-acetolactate reductoisomerase respectively, as a result of the mutation 31 . The activity of these enzymes determines the production of α-acetolactate during fermentation, which is converted to diacetyl by an oxidative decarboxylation 33 .…”
Section: Impact Of Hd On Flavourmentioning
confidence: 99%